2014
DOI: 10.1007/s10876-014-0812-3
|View full text |Cite
|
Sign up to set email alerts
|

Infra-red, NMR Spectroscopy and Transport Properties of Diphosphate NaAlP2O7

Abstract: The sodium aluminum diphosphate compound has been synthesized by the classic ceramic method and characterized by X-ray diffraction technique, IR, 31 P NMR, 23 Na NMR and impedance spectroscopy. It crystallizes in monoclinic space group P2 1/c . The MAS-NMR spectra showed two and one isotropic resonances relatives to 31 P and 23 Na, respectively, revealing the existence of two phosphorus and one sodium environments in the structure. The electrical properties of this compound have been measured in the temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…9,10 We have previously reported the electrical properties of MAlP 2 O 7 (M ¼ K, Ag, Na) compounds. [11][12][13] In the study reported here, we investigated MAlP 2 O 7 , including its electrical and dielectric properties, using impedance spectroscopy to determine the conduction mechanism. MAlP 2 O 7 can be distinguished by its crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 We have previously reported the electrical properties of MAlP 2 O 7 (M ¼ K, Ag, Na) compounds. [11][12][13] In the study reported here, we investigated MAlP 2 O 7 , including its electrical and dielectric properties, using impedance spectroscopy to determine the conduction mechanism. MAlP 2 O 7 can be distinguished by its crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…The stretched exponent has a value of one for ideal Debye relaxation. The Bergman approach, which uses a modified KWW function [ 45 ], is used to determine this parameter using the following equation (17) : …”
Section: Resultsmentioning
confidence: 99%
“…The samples were sintered according to the temperatures in Table 9 . Synthesis temperatures were selected according to 4 , 11 , 28 . Due to the high hygroscopicity of P 2 O 5, it must be synthesized in tightly closed containers.…”
Section: Methodsmentioning
confidence: 99%
“…Aluminum phosphates are present in many applications, for example in chemically bonded phosphate ceramics (CBPC) with alumina, dental cement, refractory binders, composite materials, and glass–ceramics 1 – 10 . Pyrophosphates containing aluminum and monovalent cations, such as NaAlP 2 O 7 , can be used as solid electrolytes for batteries, piezoelectric and ionic conductors 11 – 13 . Furthermore, NaAlP 2 O 7 with different doped rare earth ions has potential application in white light emitting diodes (WLEDS) 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%